Third-Degree Price Discrimination in Oligopoly When Markets Are Covered - Markus Dertwinkel-Kalt; Christian Wey (ZBW - Leibniz Information Centre for Economics, 2021)
We analyze oligopolistic third-degree price discrimination relative to uniform pricing when markets are always covered. Pricing equilibria are critically determined by supply-side features such as the number of firms and their marginal cost differences. It follows that each firm's Lerner index under uniform pricing is equal to the weighted harmonic mean of the firm's relative margins under discriminatory pricing. Uniform pricing then decreases average prices and raises consumer surplus. We provide an intriguingly simple approach to calculate the gain in consumer surplus and loss in firms' profits from uniform pricing only based on market data of the discriminatory equilibrium (prices and quantities).
Keywords: D43; L13; L41; K21; 330; Third-Degree Price Discrimination; Oligopolistic Competition; Market Integration